Assessing Endobronchial Washing Mycobacterium Tuberculosis Gene Xpert’s Role in Diagnosing Pulmonary Tuberculosis in Sputum Smear Negative Patient - Faizan, Muhammad; Amir, Muhammad; Iqbal, Muhammad; Elahi, Ehsan; Faraz, Muhammad; Janjua, Owais Amjad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To see diagnostic accuracy of GeneXpert MTB in diagnosing pulmonary tuberculosis in sputum smear negative patients. Study Design: Cross-sectional Study. Place and Duration of Study: Department of Pulmonology, Pakistan Emirates Military Hospital Rawalpindi, Pakistan from May to Oct 2024. Methodology: Patients having at least any of two clinical criteria and at least one radiological finding suspected of TB and were included. The clinical criteria comprised of intermittent fever or persistent cough for greater than 3 weeks, drenching night sweats for more than 2 weeks, HIV positive patients, weight loss greater 5% of body weight, and haemoptysis. The radiological criteria included cavitatory lesions, consolidation, pleural effusion or hilar adenopathy on chest radiographs. After initial history and investigations, all patients went through fiber optic bronchoscopy. The Lowenstein Jensen (LJ) medium was used for sample inoculation and incubated for 8 weeks. The GeneXpert MTB samples were processed as per manufacturer’s specifications. Results: In this study, one hundred and twenty-two (n=122) patients median age of 46.00(28.75-59.25) years were included. The cough 95(77.87%), fever 79(64.75%) and weight loss 74(60.66%) were common symptoms respectively. The upper lung zone 84(68.85%) and middle lung zone 12(9.84%) were commonly involved. The GeneXpert MTB was reported high positive in 41(33.61%) patients. The GeneXpert MTB was found to be 92.64% sensitive, 85.71% specific and 90.98% accurate. The positive predictive and negative predictive values were 91.30% and 90.56% respectively. Conclusion: GeneXpert MTB is a reliable tool to test smear-negative patients suspected of tuberculosis.